Kesiapan Indonesia Menghadapi Kejadian Luar Biasa Polio: Analisis - Tanoto, Agnes Margareta; Sutarto, Jeceline; Susanto, Helen (PT Kalbe Farma Tbk., 2025)
Since the launch of Global Polio Eradication Initiative (GPEI) in 1988, global polio eradication eforts have succeeded in reducing polio cases by 99% and eradicated polio virus type 2 in 2015. Although Indonesia has obtained free-polio certifcation in 2014, polio outbreaks still occur. Recent polio outbreak involved circulating vaccine-derived poliovirus (cVDPV) and vaccine-derived poliovirus type 2 (VDPV2), highlighting weaknesses in fuctuating immunization coverage and the impact of the COVID-19 pandemic, which disrupted routine immunization programs. The government’s response through the National Immunization Week (PIN) and the Outbreak Response Immunization (ORI) strategy aims to address these outbreaks, but challenges such as logistical difculties, community education, and a shortage in human resources remain signifcant. Indonesia also faces issues in ensuring consistent immunization coverage, especially in high-risk areas like Papua; difculty of communication and challenges in reaching remote areas add complexity to the fght against polio. A holistic approach involving various sectors and stakeholders, along with enhanced communication and coordination eforts, is key to addressing the future threat of polio. Agnes Margareta Tanoto, Jeceline Sutarto, Helen Susanto. Indonesia’s Readiness to Polio Outbreak.